CLINICAL AND SUBCLINICAL CHARACTERISTICS OF PATIENTS WITH OVARIAN TUMORS SURGICALLY TREATED AT HA DONG GENERAL HOSPITAL (Vietnam Journal of Community Medicine, 2026)
Objective: To describe the clinical and paraclinical characteristics of patients with ovarian tumors who underwent surgery at Ha Dong General Hospital from 2021 to 2023.Methods: A retrospective descriptive study was conducted on the medical records of 93 patients diagnosed with ovarian tumors who underwent surgical intervention at Ha Dong General Hospital from January 1, 2021, to December 31, 2023.Results: Among the 93 patients, the mean age was 39.5±14.2 years, with the 30–39 age group accounting for 43.0%. Most patients had ≥2 children (63.4%); 16.1% had never been pregnant, and 17.2% had a history of miscarriage. A history of abdominal surgery was reported in 34.4% (mainly cesarean section). The majority were still menstruating (78.5%). The main symptom was lower abdominal pain (84.9%), while abnormal vaginal bleeding was rare (2.2%). Tumors were typically soft (60.2%), mobile (63.5%), well-defined (82.8%), and tender on palpation (77.4%). Ultrasound findings showed that most tumors measured 5–10 cm (63.4%), with a mean size of 67.1±28.1 mm. Echogenic characteristics included anechoic/hypoechoic (40.9%), hyperechoic (30.1%), and mixed echogenicity (29.0%); papillary projections were observed in 2.2% of cases, and 7.5% had ascites. Tumors were located on the right side in 52.7%, left side in 38.7%, and bilaterally in 8.6%. In patients who underwent CT scans and MRI, no radiological findings suggestive of malignancy were identified. CA-125 levels were elevated (>35 U/mL) in 17.8% (mean 37.8 U/mL), while HE4 was elevated in 1.0%. Histopathological results showed that most tumors were benign: serous cystadenoma (57.0%) and dermoid cysts (34.4%). Malignancy accounted for 2.1% of cases. One case of corpus luteum cyst with torsion was recorded.Conclusion: The main clinical symptom of ovarian tumors is lower abdominal pain; tumors are typically soft, mobile, and well-defined. On ultrasound, most tumors measure 5–10 cm with diverse echogenic features. No cases suggested malignancy on CT or MRI. CA-125 and HE4 levels were rarely elevated. Histopathological findings confirmed that most tumors were benign serous cystadenomas and dermoid cysts, with a low rate of malignancy.